An Empirical Assessment of the Relationship Between Life Expectancy at Birth and Carbon Dioxide Emissions in 27 European Union Countries - Szymańska, Agata (Panoeconomicus, 2025)
The study examines the statistical significance of the effects of carbon dioxide (CO_2) emissions on life expectancy at birth, using panel data of 27 European Union (EU) countries between 1995 and 2019. The effects are analysed with two measures of CO2 emissions: metric tons per capita, and kg per 2015 USD of GDP. A set of additional determinants investigates the relationship between the dependent variable and selected controls, including the costs of living, ageing, and social support. In each estimation technique, the results indicate a statistically significant negative association between CO_2 emissions and the dependent variable. The additional estimates emphasise higher elasticities in the old EU countries compared to the new countries that joined the EU in May 2004 and later. The results suggest that socio-economic conditions alone are insufficient to stimulate health status, proxied by life expectancy; the environmental component is also important. JEL: I10, I14, J11, Q50